Università e territorio: il decentramento dell'Ateneo nella Provincia di Firenze Atti del convegno di studi Firenze, 23 gennaio 2004 - Rogari, Sandro (Firenze University Press, 2006)
The volume collects the proceedings of the conference "Università e Territorio. Il decentramento dell'Ateneo nella Provincia di Firenze ("University and Territory. The decentralisation of the University in the Province of Florence"), which was held in Florence on January 23, 2004. The conference saw a wide participation of interventions and public debate, and dealt with the issues concerning the decentralisation of educational and scientific activities in the municipalities of the Province of Florence, with particular reference to the university settlements of Calenzano, Scandicci, Sesto Fiorentino, Vaglia, Figline Valdarno, San Casciano Val di Pesa and the district Circondario Empolese Valdelsa. The conference was conceived as an occasion of meeting and dialogue between Mayors of the Province, local administrators and deans of university degree courses. It highlighted the multiplicity and differentiation of the activities as well as the complexity of the problems related to the development of study courses in the different social-economical realities of the municipalities of the Province of Florence.